Spatial regulation of ribosomal protein gene expression revealed by spatial transcriptomic analysis in the water fern Ceratopteris richardii - Han, Jin; Li, Gui-Sheng (Frontiers in Plant Science, 2026)
Spatial transcriptomics is proving to be a powerful tool in elucidating plant development complexities. A study on the water fern Ceratopteris richardii applied this technology to sporophyte development, identifying 11 distinct spot clusters that mapped to leaves at various stages and probably leaf primordia and the shoot apical meristem (SAM), the stem, the vasculature, and scales/trichomes. Several transcription factors were identified—from the ARF, GRF, AP2, and bZIP families—as marker genes for these clusters. Functional enrichment analysis of marker genes identified biologically important processes, such as chloroplast-related functions in advanced leaves and DNA helicase activity in mitotic tissues. The pervasive enrichment of ribosome-related functions in nearly all tissue domains was unexpected. Furthermore, ribosomal protein (RP) genes were differentially expressed between tissues, marking single or multiple tissues. Paralogs encoding the same type of RP also differed in expression patterns from one another, with certain members not expressed or uniformly expressed. in situ hybridization showed that RP genes were generally expressed in the SAM, leaf primordia, and the vasculature.